Plan de negocios de exportación de piña hacia Estados Unidos (2019)
This paper presents the design of a pineapple export business plan to the United States, evaluating the different variables of the market and the operational infrastructure that intervene in the development of the project. Therefore, it was necessary to identify: the characteristics of the product; the sector: national and international production; the unsatisfied demand; the trends in the market; the technology; the incentives and governmental support of both countries within the union; the market bidders; international prices; the role of substitute products in addition to national and international parameters to carry out the export process